How Does Servant Leadership Influence Employee Creativity? A Scoping Review - Wahyu Dodi Tri Marianggodo; Muhid, Abdul (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This scoping review synthesizes contemporary evidence on how servant leadership shapes employee creativity through intertwined psychological and organizational mechanisms. Covering publications from 2010 to 2025, the study systematically mapped 2,467 records retrieved from Google Scholar and ScienceDirect, screened with Publish or Perish, and managed through Mendeley. A total of 27 studies met the PRISMA-ScR eligibility criteria. The analysis reveals that servant leadership enhances creative behavior through five recurrent pathways: heightened psychological safety, strengthened psychological empowerment, increased knowledge-sharing practices, deeper engagement in creative processes, and the presence of an innovation-supportive climate. These mechanisms operate within contextual boundaries shaped by factors such as creative self-efficacy, corporate social responsibility initiatives, organizational culture, and industrial settings. The findings are conceptually grounded in three dominant theoretical frameworks—Conservation of Resources Theory, Self-Determination Theory, and Social Learning Theory—which collectively illustrate how servant leaders cultivate psychological resources, intrinsic motivation, and prosocial modeling that stimulate creativity. Overall, the review indicates that servant leadership functions not merely as a moral orientation but as a managerial strategy capable of fostering sustainable creativity through reinforced psychological and social conditions within organizations.